The Influence Of Adeno Associated Virus Vector Receptor AAVR And Co-Receptors And Their Mutations On Tropism And Transduction Of Adeno Associated Virus During Gene Therapy A Review Tirthal Rai Usha Adiga Deepika Kamath M (Journal of Pharmaceutical Negative Results, 2022)
Gene therapy is an experimental treatment being investigated to correct defective genes that are responsible for disease development. To treat cancer and genetic illnesses, researchers are looking into a variety of gene therapy techniques. Finding a proper vector to transfer DNA into tissues is one of the most difficult aspects of gene therapy. Some gene therapy vectors have issues with infecting both quiescent and dividing cells, provoking an immunological response, lack of indefinite expression, and reproducible high titre. The adenovirus, retrovirus, and recombinant modified adeno-associated virus are top contenders for gene therapy vectors (rAAV). The issues with gene therapy may be resolved by the adeno associated virus (AAV). Hemophilia is a condition which may be benefited by the gene therapy using AAV as vector. Aim of this review is to emphasize on the role of adeno associated virus receptors(AAVR) and co-receptors in tropism and transduction of adeno associated virus(AAV) in the gene therapy of hemophilia In Vitro as well as In Vivo.